Unearthed - Kaufman, Amie; Spooner, Meagan (Unearthed ;, 2018)
Scholar Jules Addison and scavenger Amelia Radcliffe join forces to unravel secrets of a long-extinct civilization, only to discover something that could spell the end of the human race.